(3NHQ GdfHjg HNHQ EaJGM GdefUhQ hHfjgs - (3eMeO Hf Ydj GdYeQGfj GdUfYGfjs ((3YHO GdQMef Hf MSjf GdTGei s)
(3ChdgG (B:s
(3GdMeO ddg GdPi EaJQO HGdHbGA hHYO , agPg hQjbGJ JVeJ CdaGXkG cdeGJgG QcjcGJ , bUOJ HgG MaX CNHGQ GdOhdI GdbGSejI ai Gdjef Ydi SHjd GdLedI s
(3BNQgG (B:s
(3hMUdfG ef eYOf GdYjhH hhLd eG EQJcHfG ai OMVg hhbYfG ajg haQZJ ef JHjVI hJUfjag eeG YSGg jJCgd deMhg Hecg GdeTQaI s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf hGdJQbje HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs